The effect of MgNPs synthesized by using green method on the produc-tion and proliferation of Capisum annuum callus culture In Vitro - Hadi, Sabah Mahdi; Rashed, Maad Abdalmonem (Journal of Kerbala for Agricultural Sciences, 2023)
Nanotechnology, consider as one of the newest important methods towards improve the production of callus using plant tissue culture. The objective of the current work was to create a unique callus induction methodology. and proliferation from Capisum annum in vitro. Therefor different concentrations of Mg nanoparticles were used which synthesized using green method. For callus inducement, young foliage, and stem from the sterile germinated seedlings using Sodium hypochlorite (NaOCL) 6% for 10 min were used as explants. They were cultivated in MS media supported by several combinations of kinetin and 2, 4- Dichlorophenoxyacetic. The maximum percentage responsive reached 100% from leaf explants at 2, 4-D 1.5 mg/L and Kin 1.0 mg/L. While 2, 4-D 1.5 mg/L and Kin 0.5 mg/L achieved the highest fresh weight for callus proliferation. The best MgNPs concentration for callus inducement and proliferation of capsicum leaves and stem explants was MS media supported with 1.0 and 0.3 ml/L respectively. While the highest proliferation mean value for callus was recorded at the concentration of 6.0 ml/L MgNPs in MS medium reached 6.1 gm. AFM photographs prove that MgNPs were in nanometer size and had the spheres and the rods shape. The average grain size of the MgNPs was 23.8 to 38.24 nm.